Which activities count? Using experimental data to understand conceptualizations of physical activity. (December 2018) - Cusatis, Rachel; Garbarski, Dana
Abstract: US health surveys consistently report that men and those with higher socioeconomic status (SES) engage in more physical activity than women and lower SES counterparts, using questions that ask about physical activity during leisure time. However, social characteristics such as gender and SES shape understandings of and access to leisure-based physical activity as well as other domains where healthy activity is available – namely house work, care work, and paid work. Thus, the physical activity of US adults may look different when what counts as physical activity expands beyond leisure activity. The current study uses Amazon's Mechanical Turk platform to conduct a 2-by-2-by-2 factorial experiment that crosses three types of physical activities: leisure, house or care work, and paid work. We find that physical activity questions that prime respondents – that is, ask respondents – to consider house/care work or paid work lead to increased minutes reported of physical activity compared to not priming for physical activity, while asking about leisure is no different from having no physical activity primed. The effect on reported physical activity of priming with house/care work is stronger for women than men, demonstrating support for gendered specialization of time spent in the house and care work domain. The effects on reported physical activity of priming with house/care work and paid work are stronger for those with less education compared to more education, consistent with socioeconomic divisions in access to physical activity in house/care work and employment. This study highlights the contingence of our understanding of the physical activity of US adults on both its measurement in surveys and the social forces which shape understanding of and access to physical activity. Highlights: Leisure questions may not capture gender and socioeconomic patterns shaping access to and opportunity for physical activity. Priming for house/care work or paid work increases minutes reported of physical activity compared to no prime. The effect on physical activity of priming respondents for house/care work is stronger for women than men. The effects on physical activity of priming with house/care work and paid work are stronger for those with less education. Understandings of physical activity of US adults relies on measurement and the social forces shaping access and opportunity.